Effect of smoking on the development of chronic obstructive pulmonary disease in young individuals: a nationwide cohort study - Chung, Chiwook; Lee, Kyu Na; Han, Kyungdo; Shin, Dong Wook; Lee, Sei Won (Frontiers in Medicine, 2023)
Background Cigarette smoking is an important risk factor for developing chronic obstructive pulmonary disease (COPD). However, the effect of smoking on the development of COPD in young individuals remains unclear. We aimed to evaluate the effect of smoking on COPD development in young individuals. Methods Using the Korean National Health Information Database, we screened individuals aged 20–39 years who participated in the national health check-up between 2009 and 2012. We defined physician-diagnosed COPD based on health insurance claims and searched the database until December 2019. We identified 6,307,576 eligible individuals, and 13,789 had newly developed COPD. We used multivariate Cox proportional hazards models to estimate the adjusted hazard ratio (aHR) of risk factors for COPD. Results The incidence rate for developing COPD was 0.26/1000 person-year. The risk of developing COPD was significantly higher in current smokers [aHR 1.46, 95% confidence interval (CI) 1.39–1.53] and former smokers (aHR 1.21, 95% CI 1.14–1.29) than in non-smokers. Furthermore, the risk increased with increasing smoking amounts (≥20 pack-years, aHR 2.24; 10–20 pack-years, aHR 1.55; <10 pack-years, aHR 1.27). Female participants had a higher relative risk of developing COPD due to smoking, compared with their male counterparts. Conclusion Cigarette smoking increased the risk of developing COPD in young individuals. Current and heavy smokers had higher risks of developing COPD than non-smokers. Female smokers were more likely to develop COPD than male smokers.